The Influence of Price, Quality, and Business Location on Fruit Buying Interest - Evriyani Audila Sipayung; Ni Luh Made Indah Murdyani Dewi (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2024)
Understanding the factors influencing consumer buying interest is necessary to attract and retain new customers. Consumers consider several factors before buying, such as price, quality, and business location. This research aims to examine the influence of price, quality, and business location partially and simultaneously on consumer buying interest from fruit traders in Badung Market. The sample was obtained using the accidental sampling method with 45 respondents. The data analysis technique is Partial Least–Structural Equation Modelling with SmartPLS4. The results conclude that price, quality, and business location simultaneously significantly affect consumer buying interest. Partially, Quality and Business Location are known to significantly influence consumer buying interest, while the price variable does not have a significant effect on consumer buying interest.